Surface Roughness and Biocompatibility of Polycaprolactone Bone Scaffolds: An Energy-Density-Guided Parameter Optimization for Selective Laser Sintering - Han, Jian; Li, Zehua; Sun, Yuxuan; Cheng, Fajun; Zhu, Lei; Zhang, Yaoyao; Zhang, Zirui; Wu, Jinzhe; Wang, Junfeng (Frontiers in Bioengineering and Biotechnology, 2022)
3D porous polycaprolactone (PCL) bone scaffolds prepared by selective laser sintering (SLS) have demonstrated great potential in the repair of non-load-bearing bone defects. The micro geometry and surface roughness of PCL scaffolds during the SLS process may change the biocompatibility and bioactivity of the scaffolds. However, in addition to the widely concerned mechanical properties and structural accuracy of scaffolds, there is still a lack of systematic research on how SLS process parameters affect the surface roughness of PCL scaffolds and the relationship between roughness and biocompatibility of scaffolds. In this study, we use the energy density model (EDM) combined with the thermodynamic properties of PCL powder to calculate the energy density range (Ed1-Ed3) suitable for PCL sintering. Five PCL scaffolds with different laser power and scanning speed were prepared, and their dimensional accuracy, mechanical strength and surface properties were comprehensively evaluated, and the bioactivities were compared through the attachment and proliferation of MC3T3-E1 cells on the scaffolds. It was found that the high energy density (Ed3) reduced the shape fidelity related to pore size and porosity, and the dense and smooth surface of scaffolds showed poor cytocompatibility, while the low energy density (Ed1) resulted in weak mechanical properties, but the rough surface caused by incomplete sintered PCL particles facilitated the cells adhesion and proliferation. Therefore, the surface roughness and related biocompatibility of PCL bone scaffolds should be considered in energy-density-guided SLS parameters optimization.